The interprovincial green water flow in China and its teleconnected effects on the social economy - S. Sang; S. Sang; Y. Li; Y. Li; C. Hou; C. Hou; S. Zi; S. Zi; H. Lin; H. Lin (Hydrology and Earth System Sciences)
Green water (terrestrial evapotranspiration) flows from source regions, precipitates downwind via moisture recycling, recharges water resources, and sustains the social economy in sink regions. However, unlike blue water, there has been limited assessment of green water flows and their teleconnected effects on the social economy. This study used a climatology mean moisture trajectory dataset produced by the UTrack model for 2008–2017 to quantify interprovincial green water flows in China and their socioeconomic contributions. Results reveal an interconnected flow network where the green water of each province reciprocally exchanges with each other. Despite self-recycling (ranging from 0.6 % to 35 %), green water mainly forms precipitation in neighboring provinces, with average interprovincial flow directions from west to east and south to north. About 56 % of the total green water exported from the 31 mainland source provinces remains at home, contributing 43 % of the precipitation in China. The green water from the source provinces embodies substantial socioeconomic value for the downwind provinces, accounting for about 40 % of the water resources, 45 % of the gross domestic product (GDP), 46 % of the population, and 50 % of the food production of China. Green water from the western provinces is the largest contributor to water resources, while green water from the southwestern and central provinces embodies the highest GDP, population, and food production. Overall, the embodied socioeconomic values of green water flow increase from the source to sink provinces, suggesting that green water from less developed provinces effectively supports the higher socioeconomic status of developed provinces. This assessment emphasizes the substantial teleconnected socioeconomic values of green water flows and the need to incorporate them towards more comprehensive and effective water resource management.